2017
DOI: 10.1186/s13104-017-2924-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and associated factors among type 2 diabetic patients at Shanan Gibe Hospital, Southwest Ethiopia

Abstract: ObjectiveThe aim of this study was to assess the rate of glycemic control and factors affecting glycemic control in type 2 diabetic patients.ResultsA total of 174 type 2 diabetic patients were interviewed and were studied. Mean age of the patients was 48.98 ± 14.96 years (range 18–80 years). More than half (51.7%) of the patients were males. About a third of patients, 53 (30.5%), were on antidiabetic medications for less than 5 years. The most common prescribed antidiabetic medications were insulin, 48 (27.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
66
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 22 publications
(20 reference statements)
18
66
2
1
Order By: Relevance
“…In the current meta-analysis, seven regions and one administrative town in the country were represented. Most studies took place in Oromia Region (n = 13) [2,17,22,25,28,29,35,37,48,49,51,52] and Amhara Region (n = 9) [4,16,20,27,34,38,44,46,53]; followed by Tigray Region (n = 4) [23,31,32,47], South Nation Nationality of People (SNNP), n = 3)) [21,26,33]; Addis Ababa (n = 4) [30,42,45,54]; Benishangul Gumuz region [24], and Harari region [1] (n = 1 each). Most studies dealt with self-monitoring of blood glucose (SMBG) (n = 21), followed by overall diabetes self-care (n = 16), assessment of dietary practice (n = 15), and engagement in physical activity (n = 14).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current meta-analysis, seven regions and one administrative town in the country were represented. Most studies took place in Oromia Region (n = 13) [2,17,22,25,28,29,35,37,48,49,51,52] and Amhara Region (n = 9) [4,16,20,27,34,38,44,46,53]; followed by Tigray Region (n = 4) [23,31,32,47], South Nation Nationality of People (SNNP), n = 3)) [21,26,33]; Addis Ababa (n = 4) [30,42,45,54]; Benishangul Gumuz region [24], and Harari region [1] (n = 1 each). Most studies dealt with self-monitoring of blood glucose (SMBG) (n = 21), followed by overall diabetes self-care (n = 16), assessment of dietary practice (n = 15), and engagement in physical activity (n = 14).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…DM self-care activities are owned by patients and their families;, as a result, there should be consistent and effective measure for diabetes self-care through dietary and lifestyle modification complemented with supportive role of health care providers [4,[13][14][15]. Self-monitoring of glycemic combined with regular physical activity are considered as a cornerstone of diabetes cares to ensure patient participation in achieving and maintaining at recommended level of blood glucose [6,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that satisfaction on doctor-patient interaction as well as the implementation of FDC were the important factors associated with T2DM patient's glycaemic control. The proportion of good glycaemic control among T2DM in Kelantan was still low as compared to another local study [12] and other countries such as Mexico, Brazil and Saudi Arabia [4,16,17]. However, the comparison must be made cautiously as other study used different cut-off point such as HbA1c of <7% to be defined as good glycaemic control as compared to this study which uses cut-off point ≤6.5%.…”
Section: Discussionmentioning
confidence: 61%
“…There are several significant factors associated with glycaemic control which has been revealed by many studies such as age, sex, duration of diabetes and educational level [4,[12][13][14][15][16]. However, to the best of our knowledge, there is scarce local evidence that examines the relationship between FDC implementation and doctor-patient interaction satisfaction towards glycaemic control among T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Despite, of the importance of good glycemic control evidence showed that there is poor glycemic control in Ethiopia [17][18][19][20]. Different studies evidenced that being unable to read and write, farmer, having poor medication adherence, duration with diabetics, and duration of diabetics treatment were the significant associated factors for poor glycemic control among type 2 diabetic patients [12,[20][21][22]. The aim of this study was to assess the level of glycemic control and its associated factors among type 2 diabetic patients attending their follow up at Debre Tabor General Hospital, Northwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%